The protection of the right to housing in the doctrine of the United Nations Committee on Economic, Social and Cultural Rights (commentary to the views of February 2021 concerning communications 85, 54 and 48/2018) (Revista de Estudios Europeos, 2022)
.
Keywords: Committee on Economic, Social and Cultural Rights; Human Rights; right to housing